Formulation and Evaluation of Tablets Compressed from Granules Prepared by Thermoplastic Granulation - Kľoc D.; Wolaschka T.; Ruttkay F. (Sciendo, 2021)
The aim of this formulation study was to determine the effect of the binder used in the preparation of granules by thermoplastic granulation on the release of propranolol from experimental tablets. Another aim was to select suitable excipients and their ratio in the granules to ensure a trouble-free formulation of the tablets. This study proved that the binder affects the flow properties of the granules, disintegration of the tablets and, subsequently, also the method of drug release, which can be used for the preparation of tablets with modified or prolonged drug release.